Analisis Kekuatan Rangka Bike Lift Terhadap Beban Alat Dan Kendaraan - Akhmadi, Amin Nur; Usman, M Khumaidi; Hendrawan, Andre Budhi (Rekayasa Material, Manufaktur dan Energi, 2020)
To lift a vehicle on a bike lift, a strong frame is needed. A bike lift is a tool for lifting a motorcycle and at the same time, it can be said as a work table. Most of the servicing and repair work of motorbikes is done under the hands, so to do this the mechanic has to sit or squat. By using a bike lift, the height of the motorbike can be adjusted according to the mechanical body posture, so that according to the service work can be done in a comfortable body position without having to squat for a long time. The purpose of this research is to get a strong frame, especially on pins that are exposed to loads from the frame and vehicles. This research uses the calculation of the load that occurs at each load point and calculates the shear stress that occurs at each load point and performs a tensile test on the pin material. The results of the study, the calculation of the largest shear stress, namely 13.26 N, occurred at the bottom pin position with a pin diameter of 10 mm. Meanwhile, from the results of the pin material testing, the shear stress in the safe material range is 354.24 N / mm2. So it can be concluded that the results of the calculation of shear stress that occurs on each bike lift frame pin using solid iron pipe or axles with a diameter of 16 mm and 10 mm, the largest shear stress that occurs on the pin is 13.26 N at the pin position 10 mm. Meanwhile, from the test results of the iron used for the pin, the shear stress in the safe range of the material is 354.24 N / mm 2. So it can be concluded that the use of solid steel pipe for axles with a size of 10 mm and is exposed to the largest shear stress from the frame load, namely, 13.26 N /mm2 is safe to use and strong to withstand the load given to the bike lift.